PELATIHAN PEMANFAATAN MANGROVE SEBAGAI ALTERNATIF PEWARNA ALAM KOPERASI BATIK TULIS KEBON INDAH KECAMATAN BAYAT, KLATEN - Yohan Wismantoro; Vincent Didiek Wiet Aryanto; Amron Amron; Nanda Adhi Purusa; Dian Indriana Hapsari; Imang Dapit Pamungkas (Bajang Institute, 2022)
This training aims to provide an understanding to batik craftsmen so that they can use mangroves as an alternative to natural dyes batik. This training includes the provision of materials related to the general description of mangroves, their benefits and how to process them into natural dyes batik. The method of implementing this activity uses seminars and questions and answers to support the participants' brainstorming. Measurement of understanding in participants using pre-test and post-test instruments. The implementation phase of this activity begins with giving a pre-test, delivering material and measuring the post-test. The results of the pre-test and post-test showed an increase in participants' understanding of 62.15 percent. Participants before receiving the training were only able to get an average score of 5.99 while after participating in the training, they could get a score of 9.63. The understanding received by the participants was better accompanied by the direct processing of mangrove waste for natural dyes batik